To perform phytochemical screening and study the antioxidant potential of isolated compound from Hemidesmus indicus - Nutan; Das, Manas Kr; Saxena, Gaurav; Kumar, Nitin (Journal of Drug Delivery and Therapeutics, 2019)
“Anantmul” is an important and widely used medicinal plant. The study aimed to determine the physicochemical composition, bioactive compounds and antioxidant activity of Hemidesmus indicus (Asclepiadaceae). The roots of the plant were collected and sequentially extracted using petroleum ether, ethyl acetate, and methanol. The preliminary phytochemical screening of extracts was carried out and found to be a good source of bioactive compounds. Biological activities of flavonoid and phenolic compounds have been discovered in several latest studies. Further phytochemical isolation was carried out, and Lupeol was isolated. Phenols are shown to be multifunctional antioxidants which will perform as singlet oxygen quenchers. Lupeol was evaluated for in-vitro antioxidant activity. It showed a correlation with antioxidant activity by DPPH (IC50 = 0.52, P 6 0.05) and H2O2 (IC50 = 0.43, P 6 0.05). The results show promising perspectives for the exploitation and use of anantmul rhizome as a constituent of anti-aging as well as anticancer diet. Keywords: Anantmul, Lupeol, Antioxidant, DPPH